GAMBARAN PERILAKU IBU TENTANG PENANGANAN AWAL DIARE DALAM MENCEGAH TERJADINYA DEHIDRASI PADA BALITA DI KELURAHAN TEGAL SARI MANDALA III KECAMATAN MEDAN DENAI TAHUN 2012 - yunika anwar; Linda Maas; Alam Bakti (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT Children under five years old are vulnerable to health problems, such as diarrhea. The problem of diarrhea is about dehydration; therefore, one of the ways how to handle it is by an early stage of handling in order to prevent dehydration. The type of the research was descriptive quantitative. The population was 185 mothers who had under-five year old children, lived at Kelurahan Tegal Sari Mandala III, and had taken their children to Tegal Sari Puskesmas in the period of one year. 50 of them were used as the samples, using simple random sampling technique. The result of the research showed the description of the respondents’ characteristics as follows: the majority (52%) of the respondents is 25 to 34 years of age, was graduated from Junior High School (36%), most of them are  working mother (46%), and most of them had lees than three children (46%). According to the respondents, the most effective information about the early handling of diarrhea was from television (68%). The knowledge of the respondents was in the moderate category (64%).  The attitude of the respondents which belonged to the moderate category was (70%).The action of the respondents which belonged to the insufficient category was (66%). It is recommended that health workers at Tegal Sari Puskesmas and the agencies related to it should provide counseling and socialization properly with the message understood by the public about the early handling of diarrhea in order to prevent children under five years old from dehydration.